Blastocystosis: principles, criteria and methods of diagnostics (Information letter) - Kyrychenko, Igor; Biriukov, Mykhailo; Pokhil, Sergiy; Tymchenko, Olena (Annals of Mechnikov’s Institute, 2025)
Establishing a diagnosis of blastocystosis is carried out taking into account epidemiological, clinical data and the results of special laboratory studies. For the diagnosis of blastocystosis, epidemiological diagnostic criteria are of limited value. The clinical diagnostic criteria for blastocystosis are considered to be the presence of at least one of several of the most typical symptoms of a gastrointestinal tract disorder (diarrhea and/or abdominal pain, spasms, bloating, nausea, unstable stools, etc.), which may be accompanied by manifestations of skin and joint damage. Laboratory criteria for establishing the diagnosis of blastocystosis include at least one of the following three: detection in the patient’s stool of a diagnostically significant number of trophozoites (vegetative cells), nucleic acids, or antigens of Blastocystis sp. by microscopic (MM), molecular genetic (PCR), and immunological (ELISA) methods, respectively. For microscopic analysis, it is necessary to collect stool samples three times at intervals of one to two days, and for the diagnosis of blastocystosis using PCR and ELISA methods, it is sufficient to examine one stool sample. In stool smear microscopy, detection of any number of amoeboid forms of Blastocystis sp. and 5 or more vacuolar or other spherical parasite cells in the “high-power field” of the microscope (×400) is considered diagnostically significant, which is comparable to the descriptive terms of the approximate number of “moderate” (3-9 objects) and “many” (≥ 10 objects) in the “oil immersion magnification field” of the microscope (×1000). The PCR and ELISA test systems used must provide accurate quantitative detection of target DNA and antigens and be approved for the diagnosis of blastocystosis. Parasitological examination of MM feces is performed in compliance with the standardized procedures of the US Clinical and Laboratory Standards Institute, and by PCR and ELISA methods – in accordance with the manufacturer’s instructions for the corresponding test systems. The results of the parasitological analysis of stool should be written out in compliance with international rules. In case of detection of Blastocystis sp. their approximate number should be indicated.